2006
DOI: 10.1196/annals.1372.025
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Atrial Natriuretic Peptide and Its Receptor Levels in Long‐Term, Streptozotocin‐Induced, Diabetes in Rats

Abstract: Diabetes mellitus (DM) shows a markedly increased incidence of cardiovascular pathology that leads to hypertension, endothelial macro- and microangiopathy, diabetic nephropathy, and myocardial infarction. Atrial natriuretic peptide (ANP), is a 28 amino acid peptide hormone synthesized mainly by the heart atria and ventricles. It has potent diuretic and natriuretic properties. In this article the effect of long-term DM on blood plasma, kidney, and heart atrial and ventricular ANP concentrations were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These findings indicate that a hyperglycemia environment induce ER-dependent death pathway activity, leading to apoptosis. To our knowledge, in normal heart, synthesis of secretory proteins is not a major function of a cardiac myocyte, but with the development of cardiomyopathy in diabetes, the heart could become a neuroendocrine organ attributed to prolonged elevation of protein synthesis such as atrial natriuretic peptide and brain natriuretic peptide (Howarth et al 2006, Obineche et al 2006 and together with other strong inducers we suggested in the introduction that the ERS may participate in the beginning of diabetic cardiomyopathy. Compared with other mechanisms, involved in the diabetic myocardial cell, ERS may have crosstalk with them; this means that ERS is not only parallel with them but also as a result and mediator for other ways to apoptosis.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…These findings indicate that a hyperglycemia environment induce ER-dependent death pathway activity, leading to apoptosis. To our knowledge, in normal heart, synthesis of secretory proteins is not a major function of a cardiac myocyte, but with the development of cardiomyopathy in diabetes, the heart could become a neuroendocrine organ attributed to prolonged elevation of protein synthesis such as atrial natriuretic peptide and brain natriuretic peptide (Howarth et al 2006, Obineche et al 2006 and together with other strong inducers we suggested in the introduction that the ERS may participate in the beginning of diabetic cardiomyopathy. Compared with other mechanisms, involved in the diabetic myocardial cell, ERS may have crosstalk with them; this means that ERS is not only parallel with them but also as a result and mediator for other ways to apoptosis.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Streptozotocin-injected rats exhibit many of the cardiovascular complications found in humans with both type 1 and type 2 diabetes. They have increased levels of cardiac and circulating natriuretic peptides 192 , 193 and inflammatory markers, such as interleukin 1, interleukin 6, and intracellular adhesion molecule 1 (194) . Blood pressure remains within normal ranges, indicating that hyperglycemia alone may be sufficient to account for the observed changes seen in the heart in this model (17) .…”
Section: Modeling Hfpef In the Lab: Different Phenotypes For A Complementioning
confidence: 99%
“…Therefore, treatment with cinaciguat showed also only a slight, non‐significant induction of cGMP excretion in diabetic eNOS KO animals. Natriuretic peptides are enhanced under diabetic conditions (Malek et al, 2019; Moore et al, 2007; Obineche et al, 2006) and are mainly responsible for release of extracellular cGMP (Chaykovska et al, 2018). So, urinary cGMP probably come mainly from particulate GC signalling and high cGMP concentrations in urine of eNOS KO mice arise from a counterregulation due to reduced NO/sGC signalling.…”
Section: Discussionmentioning
confidence: 99%